The Proximate Analysis and Sensory Evaluation of Super Seed Cookies - Khairul Ikram, Emmy Hainida; Zulhar Shah, Nurbatrisyia Md; Hashim, Wan Noor Zamran; Md Nor, Norazmir (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This study aimed to determine the nutritional content and assess the consumers' acceptance of the sensory attributes of the Super Seed Cookies, which contained sacha inchi nuts, pumpkin seeds, almonds, and oats as added ingredients. The cookie was developed by a company named Mad About Cake. The cookie was analysed by measuring its proximate composition, such as moisture, ash, crude protein, crude fiber, crude fat, and carbohydrate content. This research also discovered the consumers' acceptance of the cookies by undergoing a 7-point hedonic sensory evaluation test among 30 semi-trained panelists. The proximate analysis results revealed that the Super Seed Cookies contained 4.06±0.07% of moisture, 1.80±0.04% of ash, 0.31±0.01% of protein, 3.16±0.00% of crude fiber, 7.67±0.00% of crude fat, and 83.00±0.00% of carbohydrates. In addition, the sensory evaluation results found that the consumers neither liked nor disliked all the sensory attributes of the cookies. In conclusion, improvement of the Super Seed Cookie's nutrient contents and sensory attributes is needed to make the cookies a healthy food product choice and meet the consumer's preferences before the cookies are commercialised to the market.